Állambiztonsági Szolgálatok Történeti Levéltára . The Historical Archives of State Security Services (Hungary, 2007)
The DVD presents the Archives of the Hungarian State Security Services and by showing typical pieces of the items in repositories it gives an insight in the operation of the political police and other state security organs that were the main pillars of the past regime. The materials include over 10 hours of training films of the State Security Police (ÁVH), several hundreds of photos and studies.